Statistical analysis of the socio-demographic and economic characteristics of rural areas in Romania after Eu accession - Ionuţ Cristian Baciu; Ciprian Constantin Iftimoaei (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Today's socio-economic development leads to a dilution of the "border" between rural and urban areas, especially if we look at economically developed economies, members of the OECD and/or the most powerful economies in the world united in the G7. Technology and computerization of agriculture and related industries, urban-like living spaces, reducing disparities in quality of life between urban and urban have generated a lot of controversy around the concept of "rural space". In Romania, more than half of the population lives in rural areas above the EU average. The contribution of agriculture to GDP formation is only 4%, while the employed population in this sector is 25%. Romanian agriculture remains predominantly subsistence and large agricultural holdings administer the majority of agricultural land. External migration and migration to the urban environment have led to an aging population in rural areas. Rural areas well connected to utilities and transport infrastructure has a much greater chance of economic development. The proximity of rural settlements with large urban agglomerations is also an extra chance for rural development. Statistical analysis of the socio-demographic and economic characteristics of the Romanian rural area after the accession to the EU (2007-2017), based on the data provided by the National Institute of Statistics and EUROSTAT, complemented by a SWOT analysis will highlight recent trends and prospects on short-term rural development from a human resource perspective.
Keywords: C10; 330; statistical analysis; rural space; rural development; agriculture; land reclamation; irrigations; laws